Isu Kontemporer dalam Kajian Sosiolinguistik: Bahasa dan Gender - Bariel, Songi Saxnana; Yasmadi, Yasmadi (Universitas Lampung, 2024)
In interacting and communicating, the use of language plays a very important role. However, there are still many who experience misunderstandings in communicating in everyday life. This is due to the very broad scope of language meaning, as well as differences in language styles between individuals. There are various factors that influence this difference, such as environment, education level, gender, and so on. The purpose of this study is to identify a difference in language style between men and women. Based on the results of observations made by researchers, compared to men, women tend to look very expressive. In this study, it can be seen that there are differences in language between men and women. In terms of social position, it seems that men dominate women. Men have the freedom to speak directly, while women often do not. Men can interrupt conversations and use harsher language, while women are expected to maintain politeness and be gentle in speaking. This finding has significant implications for everyday social interactions. Differences in language styles for men and women can cause misunderstandings and tensions in interpersonal communication. In a broader context, this communication pattern reflects and reinforces gender inequality in society. This can impact power dynamics in the workplace, personal relationships, and participation in public spaces. Further research is needed to explore strategies that can bridge this communication gap and promote equality in verbal interactions between genders.Keywords: Sociolinguistics, Language, Gender